2021
DOI: 10.1111/jfpe.13818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ohmic heating on physicochemical, bioactive compounds, and shelf life of watermelon flesh‐rind drinks

Abstract: The effect of thermal treatments on physicochemical, bioactive compounds, and shelf life of watermelon flesh-rind drinks was evaluated. An attempt was made for the byproduct utilization of watermelon rind as one of the major ingredient. Three different blends of watermelon flesh and rind juices (T1(100:0), T2(90:10), and T3(80:20), respectively) were pasteurized by ohmic and thermal heating (80 ± 1 C for 3 min) and were stored at refrigerated condition for 90 days. It was found that, thermal treatments and sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…The level of reduction was significantly higher ( p < .05) in treatments with 100% WMF and 15% WMR pulp as compared to the treatments with 10% WMR powder and 6% WMR extract. The decrease in TPC and TFC results of treatment with 100% WMF was in line with the findings reported in WMR juice incorporated watermelon flesh drink during 90 days of storage (Kumar et al, 2021). During storage, the decrease in TPC and TFC could be due to the degradation and oxidation of polyphenolic compounds and their polymerization with protein.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The level of reduction was significantly higher ( p < .05) in treatments with 100% WMF and 15% WMR pulp as compared to the treatments with 10% WMR powder and 6% WMR extract. The decrease in TPC and TFC results of treatment with 100% WMF was in line with the findings reported in WMR juice incorporated watermelon flesh drink during 90 days of storage (Kumar et al, 2021). During storage, the decrease in TPC and TFC could be due to the degradation and oxidation of polyphenolic compounds and their polymerization with protein.…”
Section: Resultssupporting
confidence: 90%
“…The decline in TA could be due to the oxidation of reducing sugars and ascorbic acid, acidic hydrolysis of polysaccharides and non-reducing sugars (Kanwal et al, 2017). The results regarding the physicochemical parameters of WMR-enriched watermelon fruit butter are in agreement with the findings in grape peel jam after 60 days of storage (Amorim et al, 2019) and WMR juice incorporated watermelon flesh drink after 90 days of storage (Kumar et al, 2021). In the present study, it was found that the incorporation of WMR in the form of extracts was more effective in preserving the acidity and pH as compared to other treatments during storage.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This process could potentially lead to a partial inversion of sucrose, resulting in an overestimation of refractometer readings. A similar effect was observed in research conducted by Kumar et al (2022) [21] where the hydrolysis of sucrose to glucose and fructose increased the soluble solids content in beverages. Additionally, a slightly higher acidity was observed compared to the assumed recipe (0.65 g/100 g).…”
Section: Physicochemical Composition Of Fruit Preparations Yogurt And...supporting
confidence: 83%